Che “genere” di corti? Il festival come strumento e la forma breve come misura - Giordana, Malvina (Scenari, 2021)
Starting from Roma Tre Film Festival case study, this essay reflects on the short film as a fertile land for the development of affinities between the fields of education, theoretical reflection on the audiovisual and filmic practice. Considering the expressive freedom of the short duration as a possibility to weave cinematic ambition and aesthetic experimentation, the paper focusses on the three winning short films and on some others present in the competition highlighting the hybrid elements and narrative strategies intrinsically linked to the “short” form.